Scales for rectangular horns. - Milligan, Tom (IEEE Antennas & propagation magazine.)
The scales presented are useful both for design of optimum horns for a given gain, and for finding the gains of rectangular horns from the dimensions. This article further illustrates the relationships among various parameters of rectangular horns. Although the design method started with a waveguide width-to-height ratio of 2:1, the method produces suitable designs for other waveguide ratios.